CI-groups with respect to ternary relational structures - Dobson, Edward (Ars mathematica contemporanea, 2013)
We find a sufficient condition to establish that certain abelian groups are not CI-groups with respect to ternary relational structures, and then show that the groups ?$\mathbb{Z}_3 × \mathbb{Z}_2^2$?, ?$\mathbb{Z}_7 × \mathbb{Z}_2^3$?, and ?$\mathbb{Z}_5 × \mathbb{Z}_2^4$? satisfy this condition. Then we completely determine which groups ?$\mathbb{Z}_2^3 × \mathbb{Z}_p$?, ?$p$? a prime, are CI-groups with respect to color binary and ternary relational structures. Finally, we show that ?$\mathbb{Z}_2^5$? is not a CI-group with respect to ternary relational structures.
Keywords: CI-group; ternary relation